The contribution of Arabic middle-school curricula in the KSA in developing risk management skills from the view of teachers in light of Covid-19 pandemic - Al Ayed, Khalil Mohammed Abdullah; Mahdi, Mahdi Mani (Journal of Curriculum and Teaching Methodology, 2022)
The current study aims to identify the contribution of Arabic middle-school curricula in the KSA in developing risk management skills from the view of teachers in light of Covid-19 pandemic. The sample consisted of 240 Arabic teachers in Khamis Mushait department of education. A questionnaire was used as the study tool. The questionnaire consisted of 5 dimensions and 24 indicators. Pearson correlation, Alpha-Cronbach, average, relative weights of averages, columns, standard deviation, and the outweighing relative weight of averages. The main results were: there is a medium contribution for the skills of facing stress and innovative thinking, and a low contribution for courses in the following skills: effective contact and communication, boosting team spirit and collective work, and time management. In light of results, the researchers provided some recommendations: reconsidering Arabic curricula to raise awareness of crises management skills and relevant concepts.
Keywords: Arabic curricula; middle school; Covid-19; Contribution